PENGARUH SUPLEMENTASI MINYAK KELAPA SAWIT DAN MINYAK IKAN TERPROTEKSI DALAM KONSENTRAT TERHADAP KUALITAS SEMEN KAMBING PERANAKAN ETTAWA - Anwar, Saiful (Universitas Kanjuruhan Malang, 2014)
The research was conducted at Desa Suru Kecamatan Doko Kabupaten Blitar on January 26, 2012 until February 26, 2012. The research was to determine the quality of spermatozoaofHybrid Ettawa Goat sperm with the effect of protected palm and fish oil in concentrate on the quality of Hybrid Ettawa Goat sperm. The subjects were five Hybrid Ettawa Goats that were distributed randomly to five trial groups.The research method was completely randomized design (CRD) with three trials and each trial was repeated three times. The experiment used palm and fish oil. Protected palm and fish oil were given 4% of weight. Analyzed variable in this research was the evaluationof macroscopic and microscopes of sperm quality. The data obtained were investigated by random investigation. The result of the research showed that there was no significant or real effect (P>0.05) of protected palm and fish oil supplementation in concentrate on Hybrid Ettawa goats and no significant or real interaction (P>0.05) on motility, viability, and abnormalities of Hybrid Ettawa Goats. The conclusion of the research was that the protected palm and fish oil supplementation in concentrate did not influence on Hybrid Ettawa Goats sperm quality.Â KeywordÂ : concentrare, sperm quality,fish oil, palm oil, supplementation.